Financial distress and audit fees: new evidence of the role of firm size - Azadeh Shemshad (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: Financial distress can increase investment risk for investors. Therefore, it will be necessary to review the financial statements by an independent person. Therefore, the purpose of this research is to investigate the relationship between financial helplessness and audit fees. It also examines the effect of firm size in this regard. The bigger or smaller the companies are, they can be influential in this regard.Methodology: Multivariate linear regression was used to test the two hypotheses of this research. The statistical population was 130 companies listed to the Tehran Stock Exchange during 2013-2022 (1300 firm-year observation). Altman's model [1] has been used to measure financial helplessness.Findings: The results of the research indicate the existence of a positive and significant relationship between financial distress and audit fees. The results showed that firm size can moderate the relationship between financial distress and audit fees. The results of additional tests exhibit that the difference between the size of the firm, that is, large and small and medium, has a significant difference in this regard.Originality/Value: When companies are in financial trouble, they pressure auditors to reduce their fees. This research achievement can convey essential knowledge to the users of financial statements and auditors.